TECHNOLOGY OF ENZYME TREATMENT FOR COLLOID FLUIDING IN FRUIT JUICES - Mexmonov Baxtiyor Ikromjon o’g’li; Kanoatov Xayrullo Murodillayevich (TADQIQOTLAR, 2025)
Abstract: Objective. Our article provides information on how to increase the clarity of juice by treating it with pectinase enzyme against clouding with medical colloid. Pectinases are one of the important and inexpensive enzymes of the industrial sector, especially in the fruit juice industry, they are an important enzyme for clarifying and stabilizing juices with high yields. Because pectinases are produced during the natural ripening process of fruits, we chose this enzyme for our experiment.